Recent advances in supercapacitors based on MXene surface modification: A review of symmetric and asymmetric electrodes material - Ghobad Behzadi pour; Leila Fekri aval (Results in Engineering)
MXene-based supercapacitors utilize symmetric or asymmetric electrodes. Symmetric electrodes use the same MXene material for positive/negative electrodes, providing balanced performance and stability. Asymmetric electrodes incorporate different MXene materials or combine MXene with other substances to enhance energy density (ED), stability, specific capacitance (SC), and power density (PD). The symmetric and asymmetric configurations make MXene-based supercapacitors versatile for various applications. In this review, we have summarized MXene-based supercapacitors using symmetric and asymmetric electrode materials. A comparative study has been done on the surface modification of the MXene-based supercapacitor electrodes using doping, polymer decorations, anchoring of nickel materials, and coupled carbon nanomaterials methods. The discoveries from this research serve as an invaluable reference for upcoming researchers, contributing to their comprehension of the performance and potential applications of MXene electrodes of supercapacitor technology.